2021
DOI: 10.1180/mgm.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of gold ions and gold nanoparticles to golden perch larvae (Macquaria ambigua)

Abstract: Golden perch (Macquaria ambigua) is a freshwater game-fish native to central and southeast Australia. Larvae of this fish species were used in two different types of experiments to evaluate the effects of short-term exposures (up to 6 days) to aqueous gold, 5 nm gold nanoparticles (AuNPs), or 50 nm AuNPs. Relative to the control, increased gold concentrations corresponded with yolk-sac edema (swelling). Larvae exposed to 50 μM of 5 nm AuNPs had yolk-sacs that were ~1.5 times larger resulting in the appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In the case of silver (Ag), Ag NPs are a noted anti-bacterial agent (Desireddy et al, 2013;Xu et al, 2020) and their behaviour in the environment is markedly different from macroscopic Ag, which is comparatively unreactive (McGillicuddy et al, 2017;de Souza et al, 2019). Studying metals such as Au (Reith et al, 2013;Kato et al, 2019;Sanyal et al, 2019;Shuster et al, 2021) and Pt (Reith et al, 2014(Reith et al, , 2019Asztemborska et al, 2015;Ksią żyk et al, 2015) has also led to a new understanding of environmental behaviour and toxicity of elements previously thought to be inert in natural contexts. Missen et al (2022) observed Te NPs on the surface of native tellurium grains (i.e., coarse-grained Te 0 formed from hydrothermal fluids) undergoing weathering at the Bambolla mine, Moctezuma, Mexico (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of silver (Ag), Ag NPs are a noted anti-bacterial agent (Desireddy et al, 2013;Xu et al, 2020) and their behaviour in the environment is markedly different from macroscopic Ag, which is comparatively unreactive (McGillicuddy et al, 2017;de Souza et al, 2019). Studying metals such as Au (Reith et al, 2013;Kato et al, 2019;Sanyal et al, 2019;Shuster et al, 2021) and Pt (Reith et al, 2014(Reith et al, , 2019Asztemborska et al, 2015;Ksią żyk et al, 2015) has also led to a new understanding of environmental behaviour and toxicity of elements previously thought to be inert in natural contexts. Missen et al (2022) observed Te NPs on the surface of native tellurium grains (i.e., coarse-grained Te 0 formed from hydrothermal fluids) undergoing weathering at the Bambolla mine, Moctezuma, Mexico (Fig.…”
Section: Introductionmentioning
confidence: 99%